Nonnus of Panopolis in Context III : Old Questions and New Perspectives - Doroszewski, Filip (Mnemosyne, Supplements Ser, 2020)
Intro -- ‎Contents -- ‎Preface -- ‎Figures -- ‎Abbreviations -- ‎Notes on Contributors -- ‎Introduction. Solved and Still Unsolved Issues about Nonnus and His Works (D'Ippolito) -- ‎Part 1. Nonnus and the Literary Tradition -- ‎Chapter 1. "Breaking the Fourth Wall": On Literariness and Metalepsis in Nonnus' Dionysiaca (Verhelst) -- ‎Chapter 2. Junctures of Epic and Encomium in the Dionysiaca: The Episode of Staphylos (Miguélez-Cavero) -- ‎Chapter 3. Aura's Metamorphosis in the Dionysiaca of Nonnus: A Tale of Classical and Christian Resonances (Lefteratou) -- ‎Chapter 4. I Alone Had an Untimely Love: The Ephebic 'Epyllia' of Dionysiaka 10-11 (Acosta-Hughes) -- ‎Chapter 5. Nonnus' Dionysiaca and the Latin Tradition: The Episode of Ampelus (Carvounis and Papaioannou) -- ‎Chapter 6. Nonnus and Coptic Literature: Further Explorations (Agosti) -- ‎Part 2. Literary Structure and Motifs in the Dionysiaca -- ‎Chapter 7. Visualizing Actaeon: The Motif of Recognition in Nonnus' Treatment of the Metamorphosis (Schoess) -- ‎Chapter 8. Structure and Meaning through Analogy: Remarks on the Use of Spatial Form in the Dionysiaca (Geisz) -- ‎Chapter 9. Some Aspects of Nonnus' Poetics: Antitypical Poetry in the Dionysiaca (Egetashvili) -- ‎Chapter 10. Ἁρμονίη κόσμου and ἁρμονίη ἀνδρῶν: On the Different Concepts of Harmony in the Dionysiaca of Nonnus (Otlewska-Jung) -- ‎Chapter 11. The Awakening of Ariadne in Nonnus: A Deliberate Metaphor (Hernández de la Fuente) -- ‎Chapter 12. Female Characterization and Gender Reversal in Nonnus and Colluthus (Cadau) -- ‎Chapter 13. Nonnus' Europa and Cadmus: Re-configuring Masculinity in the Dionysiaca (Hadjittofi) -- ‎Part 3. Exegesis through Paraphrase -- ‎Chapter 14. Ἀληθείῃ καὶ πνεύματι (Par. 4.114): Some Doctrinal Issues in Nonnus' Paraphrase and Their Theological Implications (Franchi).